Uso de contêiner para a otimização da eficiência energética em aviários de frango de corte: uma modelagem computacional - Meulam, Julie Cristina de Oliveira (2021)
The current poultry facilities aim to improve the performance of broilers and reduce costs to farmers. However, this generates large energy costs, especially to perform climatic adjustments such as heating, cooling, ventilation and lighting, which are necessary to maintain the thermal comfort of the birds. In Brazil, the Western region of Paraná stands out as the largest producer of poultry in the state, so this study aims to propose a project to minimize costs and make the poultry house more energy efficient. Given the above, the objective of the study was to develop two models of aviaries (dark house and container), through computer simulation, and make a comparison between these models to verify the energy efficiency and environmental comfort for the birds, thus minimizing the energy costs to the producer. For that, the study analyzed the dark house model, already existing in the market, and the model proposed for this work, composed of containers, in order to reuse existing materials that will remain in nature for many years. These models were developed using Revit software, and the energy analysis was performed using the Green Building Studio program, both from Autodesk®. The used method consisted of comparing models and analyzing the building's energy consumption throughout the year. The results concluded that the containerized aviary model was efficient in blocking solar radiation, but it uses more energy for lighting than the conventional model. The container model had the birds as the main responsible for the heat gain, and the walls and doors as the main means of temperature loss. In the dark house model, the walls, lighting, and feed were the main responsible for the heat gain, and the main factor of heat loss were the side closures and the roof of the building. Overall, the container model proposed for this study is 13.54% more efficient than the dark house model.